Igor Ivan Sikorsky papers - Sikorsky, Igor Ivan, 1889-1972.; Sikorsky, Igor Ivan, 1889-1972.
Correspondence, speeches, writings including the original manuscript of Sikorsky's autobiography, The Story of the Winged-S; An Autobiography (1938), engineering sketch books, photographs, and other papers relating chiefly to Sikorsky's activities as a pioneer in aviation especially in the development of the helicopter and to his company, Sikorsky Aviation Corporation, later United Aircraft Corporation's Sikorsky Aircraft Division. Documents his work relating to military aviation.
Engineer, inventor, and pioneer of aviation.
Collection material in English.
Keywords: Sikorsky Aviation Corporation; United Aircraft Corporation. -- Sikorsky Aircraft Division; Aeronautics; Aeronautics, Military; Aircraft industry -- United States; Airplanes; Helicopter industry -- United States; Helicopters; Sikorsky helicopters; Engineers; Inventors